An acousto-electric effect logging detector in boreholes. (10th March 2017) - Lu, Junqiang; Ju, Xiaodong; Men, Baiyong; Zhao, Honglin; Qiao, Wenxiao; Duan, Wenxing
Abstract: An acousto-electric effect logging detector in boreholes is introduced. The detector can measure the first and second type of acousto-electric effect in the downhole. The acoustic transducer of the detector is composed of a transmitting transducer T and a receiving transducer array R1, R2, and R3, and the electrode is composed of power supply electrodes A and B, and measuring electrodes E1, E2, E3, and E4. The minimum spacing between the transmitter transducer T and the receiving transducer R1 is 2500 mm, and the spacing between the receiving transducer is 300 mm. The spacing of the power supply electrode is 1500 mm, and the spacing of the measuring electrode is 300 mm. The detector circuits include the acoustic transducer excitation circuit, power supply electrode excitation circuit, acoustic signal-processing and acquisition circuit, electrical signal-processing and acquisition circuit, system main control circuit, and telemetry interface circuit. Laboratory and field tests were conducted. The sound pressure of the acoustic transmitting transducer at 1 m is up to 70 kPa. The typical acousto-electric logging signal has been observed from the field test in the downhole formation.